Handbook of research on solar energy systems and technologies - Anwar, Sohail; Efstathiadis, Harry; Qazi, Salahuddin, 1938-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This reference serves as a one-stop resource for the latest information regarding different topical areas within solar energy, emphasizing the application of nanotechnology innovations to solar energy technologies, exploring current and future developments in third generation solar cells, and providing a detailed economic analysis of solar energy applications"--Provided by publisher.
Control and conversion of solar power / Liping Guo -- Solar energy storage: an approach for terrestrial and space applications / Ahmed Elgafy -- Solar photovoltaic servo tracking controlled system / Murad Shibli -- Power electronics and controls in solar photovoltaic systems / Radian Belu -- Photovoltaic devices / Ashraf Uddin -- Nanotechnology for photovoltaic energy: challenges and potentials / Salahuddin Qazi, Farhan A. Qazi -- CuInGaSe Based thin films for photovoltaic solar cells / Harry Efstathiadis, Adam Filios -- Nanoparticle scattering, absorption, and interface effects for surface plasmon enhanced thin silicon solar cells: theory, past findings, and future directions / Nirag Kadakia -- Nanotechnology and polymer solar cells / Gavin Buxton -- Low-cost III-V compound semiconductor solar cells: progress and prospects / Michael G. Mauk -- Materials characterization techniques for solar cell devices: imaging, compositional and structural analysis / Michael S. Hatzistergos -- Mechatronics technology for solar cells / H. Henry Zhang, Danny Rodriguez, Qiong Li -- Computer simulations of solar energy systems / Akram Gasmelseed -- Image processing for solar cell analysis, diagnostics and quality assurance inspection / Michael G. Mauk -- Artificial intelligence techniques for solar energy and photovoltaic applications / Radian Belu -- Methods of forecasting solar radiation / Rubita Sudirman, Muhammad Noorul Anam Mohd Norddin -- Greenhouse solar thermal application / Tribeni Das, Ganesh C. Bora -- Technology selection for solar power generation in the Middle East: case of Saudi Arabia / Tugrul Daim ... [et al.] -- Solar energy education and training programs in the USA: an academic perspective / Sohail Anwar, Shamsa S. Anwar -- Project-based international collaboration in solar energy education: a case study from France / Sohail Anwar, Patrick Favier, Desire D. Rasolomampionona.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 18, 2012).
Keywords: Solar energy; Economics; Hybrid thermo-photovoltaic energy conversion; Nanostructures for solar energy conversion; Photovoltaic devices; Photovoltaic modules and systems; Reliability and testing standards; Solar cells; Solar energy conversion materials; Solar energy storage; Solar thermal systems; Electronic books